Pengaruh Pendekatan Creative Problem Solving Terhadap Kemampuan Berpikir Kreatif Matematik Dan Kemandirian Belajar Siswa SMP - Eni Karyuniati (Journal on Education, 2019)
The aim of this study were to find out and to examine the achievement of mathematical creative thinking skills and learning independency of junior high school students. The students were observed by using the Creative Problem Solving Approachment. The results were compared to those who use ordinary learning. The observations were done towards learning activities with contextual approaches and differences in learning independency. This research used a quasi-experimental method with a post-only control group design. Samples were taken by purposive sampling towards junior high school students. The subjects of this research were 7th grade students of SMPN 23 Bandung. The instruments used in this study were tests of mathematical creative thinking, scale and attitude about learning independency. Based on the results of data analysis towards 69 students using SPSS ver 22: Kolmogorov-smirnov test and Mann Whitney test, it was concluded that different learning methods gave different influences in students’ mathematical achievement especially in fraction. The mathematical creative thinking among middle school students who use the Creative Problem Solving approach is better than students who use ordinary learning.